2006
DOI: 10.1089/jmf.2006.9.33
|View full text |Cite
|
Sign up to set email alerts
|

Taurine-Responsive Genes Related to Signal Transduction as Identified by cDNA Microarray Analyses of HepG2 Cells

Abstract: Taurine-induced changes in the expression profiles of HepG2 cells were assessed using a cDNA microarray technology, and confirmed by real-time reverse transcription-polymerase chain reaction (RT-PCR) analyses. Of 8,298 human genes on the microarray, 128 genes (87 known genes) were up-regulated, and 349 (206 known genes) were down-regulated more than 2.0-fold by taurine. Among the 293 known genes regulated by taurine, a total of 44 genes were involved in signal transduction; 16 genes were up-regulated greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…However, our results do not exclude the increase in calpastatin expression during focal cerebral ischemia. The mechanism by which taurine increases calpastatin actions is unclear, which might be related to the up-regulation of gene expression by taurine (Park et al 2006), or down-regulation of calpain and caspase-3 activation by taurine, as demonstrated in this study. Further study is needed to determine the mechanism by which taurine up-regulates the calpastatin actions during focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 74%
“…However, our results do not exclude the increase in calpastatin expression during focal cerebral ischemia. The mechanism by which taurine increases calpastatin actions is unclear, which might be related to the up-regulation of gene expression by taurine (Park et al 2006), or down-regulation of calpain and caspase-3 activation by taurine, as demonstrated in this study. Further study is needed to determine the mechanism by which taurine up-regulates the calpastatin actions during focal cerebral ischemia.…”
Section: Discussionmentioning
confidence: 74%
“…Physiological roles of Tau include membrane stabilization, osmoregulation, neuromodulation, regulation of calcium homeostasis, and antioxidation (Bouckenooghe et al, 2006). Previous study also showed that Tau might act on various cellular processes such as proliferation, differentiation and inhibition of apoptosis (Park et al, 2006). Reduced Tau signal in degenerating rat brain with Alzheimer's disease was also reported recently using 1 H MRS (Labak et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…In non-placental cells, intracellular taurine modulates the expression and phosphorylation of proteins involved in the MAPK, STAT3 and PKC signalling pathways. 21 Each of these signalling molecules are involved in cell differentiation, 22, 23, 24 therefore, alterations in intracellular taurine could affect their role in this process. Alternatively, taurine could help maintain gap junctional intercellular communication required for cell fusion, as has been shown in liver.…”
Section: Discussionmentioning
confidence: 99%